(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to analyze the BMI and the waist girth as overweight indicators of risk for the development of diseases related to the excess of central body fat in soccer referees from the Paraná Soccer Federation (FPF). Sample was composed by 88 male referees. Weight, Height and waist girth were measured. BMI mean was 24,9±2,8 kg/m2, considered normal by health standards. However, just 55% of the referees showed values inside in health standards. There is a statistical significance between groups normal and over BMI standards (p<0,0001). Waist girth mean was 87,0 ± 8,0 cm. Although, two referees showed values over 102 cm, in other words, consider with high risk by development of degenerative diseases, obtained by association between BMI and of central body fat (waist girth).